Autoand heterosuggestion in boat rowing - V.I. Omelyanenko (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
Purpose. Creation of a complex integrated person-centered psychological model of sportsmen preparation for competitions in rowing and canoeing on base of geterosuggestion which includes psychological methods and their modifications as well as Rajah yoga system mindset trainings. Material, methods. In research took part 20 sportsmen in boat rowing of 1 st juinor category aged 15 and 16 years old with parental consent. Different variants of combinations of psychological techniques developed psychotherapist with the participation of the team's coach, taking into account specific situations arising for each athlete individually. Results. Found that the experimental group was superior to the competition in scoring control group. Correction rowing technique was observed within 1-3 sessions. An efficiency of use of the developed model in the psychological preparation of rowers. Successfully carried out programming, simulation , correction of motor skills and psycho-emotional state of athletes in training and competitive periods. Conclusions. Stability of high sports results observed on the background of the post-hypnotic suggestion and formed a positive psycho-emotional and motivational attitude. The advantage over geterosuggestion under autosuggestion.